GOOD MONEY HABITS IN SUPPORTING SHARIA FINANCIAL PLANNING - Habibie, Azwansyah (NUSANTARA : Jurnal Ilmu Pengetahuan Sosial, 2024)
Financial planning is an indicator of creating good human habits by using secondary and primary data. This research uses observation and interview data collection techniques with the research results that in making sharia financial planning according to Islamic law we must be able to prioritize needs, live simply, have 10 emergency funds, immediately look for additional work when financial conditions are felt to be unstable, debt management is no more than 30 percent and when you have emergency funds you will invest in sharia products.